Advanced Net Flux Radiometer for the Ice Giants - Aslam, S; Achterberg, RK; Calcutt, SB; Cottini, V; Gorius, NJ; Hewagama, T; Irwin, PG; Nixon, CA; Quilligan, G; Roos-Serote, M; Simon, AA; Tran, D; et al. (Springer, 2020)
The design of an advanced Net Flux Radiometer (NFR), for inclusion as a payload on a future Ice Giants probe mission, is given. The Ice Giants NFR (IG-NFR) will measure the upward and downward radiation flux (hence net radiation flux), in seven spectral bands, spanning the range from solar to far infra-red wavelengths, each with a 5° Field-Of-View (FOV) and in five sequential view angles (±80°, ±45°, and 0°) as a function of altitude. IG-NFR measurements within either Uranus or Neptune’s atmospheres, using dedicated spectral filter bands will help derive radiative heating and cooling profiles, and will significantly contribute to our understanding of the planet’s atmospheric heat balance and structure, tropospheric 3-D flow, and compositions and opacities of the cloud layers. The IG-NFR uses an array of non-imaging Winston cones integrated to a matched thermopile detector Focal Plane Assembly (FPA), with individual bandpass filters, housed in a diamond windowed vacuum micro-vessel. The FPA thermopile detector signals are read out in parallel mode, amplified and processed by a multi-channel digitizer application specific integrated circuit (MCD ASIC) under field programmable gate array (FPGA) control. The vacuum micro-vessel rotates providing chopping between FOV’s of upward and downward radiation fluxes. This unique design allows for small net flux measurements in the presence of large ambient fluxes and rapidly changing ambient temperatures during the probe descent to ≥10 bar pressure.